Comparison between subjective and quantitative methods for assessing the resolution limit of radiographic systems - Alvarez, Matheus; de Oliveira, Marcela; Pina, Diana R.; Miranda, José R. A. (Revista Brasileira de Física Médica, 2015)
The aim of this study was to compare two ways of measuring the resolution limit of radiographic systems, one subjective and one quantitative. To this end, nine images were acquired with different radiographic techniques using a pattern of bars and aluminum plates. With these images were acquired modulation transfer function (MTF) through the edge image obtained by the aluminum plate — the MTF 10% was measured on all images — and the variation of these points, which was faced with the evaluation obtained by the resolution limit of the standard bar. Although we have observed a greater variation between measurements obtained using the bar-pattern, the simplicity of this measuring technique favors the common use of the same. We concluded that, to optimize the quality control of radiographic equipment, it is suggested to measure the MTF at least in periods of time while the annual pattern of bars to be used in shorter time periods to measure changes in resolution of the system.